Parasite transmission by arthropods - Reisen, William K. (Henry Stewart Talks, 2010)
Parasite acquisition, mouthparts and blood feeding, Modes of parasite replication and transmission in the arthropod and vertebrate hosts, Factors affecting the efficiency of transmission, Role of humans: anthroponoses vs zoonoses, Intrinsic and extrinsic incubation
Reviewed at 2020/06/15